Klasse II:1 Behandlung mit der Begg-Technik und Extraktion der Sechsjahrmolaren im Oberkiefer - Mechanismus von Lückenschluss und Overjetkorrektur : Eine röntgenkephalometrische Untersuchung - Knieling, Caroline; Justus Liebig University Giessen (My University, 2005)
Ziel: Ziel der Studie war, das Ausmaß der sagittalen Okklusionsveränderungen bei Patienten mit einer Klasse II:1 zu ermitteln, die durch Multibracket-Apparatur und Extraktion der oberen ersten bleibenden Molaren therapiert wurden. Material und Methode: Von 62 Patienten im Alter von 11-15 Jahren wurden Fernröntgenseitenbilder von vor (T1) und nach (T2) der Behandlung ausgewertet. Die Auswertung erfolgte anhand der SO-Analyse von Pancherz (PANCHERZ, H.'The mechanism of Class II correction in Herbst appliance treatment. A cephalometric investigation.' Am. J. Orthod. 82: 104-113, 1982). Ergebnisse: Bei allen Probanden kam es zu einer Verkleinerung des Overjets von 5,4 mm, davon waren 79 % dental und 21 % skelettal bedingt. Die Korrektur der Molaren-Relation betrug 6,6 mm in Richtung Klasse II, welche sich erklären aus 117 % dental und 17 % skelettal. Die Prämolaren-Korrektur lag bei 4,6 mm in Richtung Klasse I mit einer Beteiligung von 25 % skelettal und 75 % dental. Der Lückenschluss fand zu 83 % durch Molaren-Bewegung und zu 17 % durch Prämolaren-Bewegung statt. Diskussion: Die Ergebnisse zeigen, dass der Erhalt einer Klasse I-Relation und ein Lückenschluss nach kieferorthopädischer Extraktion sowohl durch Mesialbewegung der oberen zweiten Molaren als auch durch Distalbewegung der oberen zweiten Prämolaren erlangt wird.

Aim: To analyse the following changes occuring during Class II, division 1 treatment with the Begg-method in combination with extraction of maxillary permanent first molars: (1) skeletal and dental components involved in overjet correction and (2) mesial and distal tooth movements contributing to extraction space closure. Subjects and Methods: From 62 subjects lateral head films from before and after treatment were scrutinized using the SO-Analysis of PANCHERZ (1982)*. Results: (1) The overjet was, on average, reduced by 5.4 mm (p<0,001). This was accomplished by advancement of the mandibular base by 1.6 mm (31%), counteracted by retrusion of the maxillary base by 0.5 mm (-10%), retrusion of the maxillary incisions by 3.0 mm (56%) and protrusion of the mandibular incisiors by 1.3 mm (23%). (2) Maxillary extraction space closure, by an average, of 10.9 mm (p<0.001) was accomplished by mesial second molar movements of 9.0 mm (83%) and distal second premolar movements of 1.9 mm (17%). Conclusion: In the present Class II, division 1 sample treated by maxillary first molar extractions and the Begg-mechanism overjet correction was accomplished by 79% dental and 21% skeletal changes. Extraction space closure resulted from 83% mesial second molar movements and 17% distal second premolar movements.* PANCHERZ, H.: The mechanism of Class II correction in Herbst appliance treatment. A cephalometric investigation. Am. J. Orthod. 82: 104-113, 1982
Class II, Division 1 maxillary first molar extraction treatment - Mechanism of overjet correction and extraction space closure
Keywords: ddc:610